2018
DOI: 10.3190/jgeosci.260
|View full text |Cite
|
Sign up to set email alerts
|

The crystal-chemical autopsy of octahedral sites in Na-dominant tourmalines: octahedral metrics model unconstrained by the Y,Z-site disorder assignment

Abstract: The structure of tourmaline-supergroup minerals includes two types of octahedral sites: the ZO 6 octahedron is smaller and more distorted than the YO 6 octahedron. The octahedral sites metrics were studied and their dependency on the chemical composition unconstrained by Y,Z-site disorder assignment. Published chemical and structural data were collected from American Mineralogist Crystal Structure Database for tourmaline samples belonging to dravite-schorl, schorl-elbaite (including tsilaisites) and schorl (± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…These variations mainly occur at the shared edge of the ZO 6 and YO 6 octahedra -not only at the O3, but also at O6 site (Bačík 2018). Moreover, the Z-and Y-site occupancy influences the distortion at the neighboring sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These variations mainly occur at the shared edge of the ZO 6 and YO 6 octahedra -not only at the O3, but also at O6 site (Bačík 2018). Moreover, the Z-and Y-site occupancy influences the distortion at the neighboring sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, both the Z-O3 and Z-O7' bonds are longer. The Z-O3 bond length is expanded due to OH group dominance at the O3 site, which also causes the elongation of the Z-O7' bond (Bačík 2018). The O-H bond valence, which is slightly lower than 1 vu due to the hydrogen bond, reduces in the Z-O3 bond valence to 0.36 vu (Bačík 2018).…”
Section: Determination Of the "Goldilocks Zone" For Crystallographic mentioning
confidence: 99%
See 2 more Smart Citations
“…Bond valences attached to the graph edges were derived from [46,47] for V-and W-site bonds and [48,49] for Z-and Y-site bonds. X-site valences were calculated from the structure of fluor-schorl [50] and olenite [51] which have the highest Na content at the X site from the whole dataset of [49]. The calculation revealed that the X-O2 bond valence is 0.14 vu (valence units) in both samples, while X-O4 and X-O5 bonds have valences between 0.07 and 0.09 vu.…”
Section: Pb 2+ and Bi 3+ At The X Sitementioning
confidence: 99%